(ctg(4*pi/3)-3*tg(2*pi)+sin(11*pi/3))*cos(-7*pi/6) =
(ctg(pi/3)-3*tg(0)-sin(pi/3))*(-cos(pi/6)) =
(1/корень(3) -3*0-корень(3)/2)*(-корень(3)/2) =
(корень(3)/6)*(корень(3)/2) = 3/12=1/4=0,25
cos(0,3)+cos(pi-0,3)-sin^2(2)-cos^2(2) = cos(0,3)-cos(0,3)-1=-1
cos(-7*pi/9)ctg(12*pi/5)tg(3)=(-)*(+)*(-)=(+) > 0
tg(-1)*cos(7)*ctg(2)=(-)*(+)*(-)=(+) > 0
cos(6) и sin(8)
cos(6)=cos(2*pi-6)=sin(6-3*pi/2)
0<6-3*pi/2 <pi/2<br>6-3*pi/2=1,28761102
sin(8)=sin(8-2*pi)=sin(3*pi-8)
0<3*pi-8 <pi/2<br>3*pi-8 =1,424777961
sin(8)>cos(6)